Is maternal therapeutic opioid use instigating misdiagnosis in breastfed infants? A case report - Ahmadzai, Hilai; Crowe, Andrew; Tee, Lisa (Australian Breastfeeding Association, 2020)
Despite the known risks associated with opioid use during breastfeeding, their place in therapy is established as part of a multimodal approach to treatment of pain in the early postpartum period. Opioids may be prescribed for post- caesarean analgesia without adequate patient education, resulting in adverse drug events in breastfed infants. We report the case of an exclusively breastfed 6-day-old infant who presented with symptoms of progressive drowsiness, somnolence and inability to feed. Maternal medication use was discounted as a potential causative factor and it was not explored further, despite the mother taking a long-acting opioid at the time. A series of invasive investigative tests were carried out and the infant was commenced on intravenous antibiotics for suspected sepsis. All test results were negative for infections and no causes for the symptoms. The infant was discharged 3 days later with a formal diagnosis of a ‘probable viral infection’. A lack of understanding by healthcare professionals of the impact of maternal medication use (particularly drugs with known risks) on breastfed infants can result in infant ADE, inappropriate prescribing, stress and anxiety for new parents and a lost opportunity to contribute to lactation- related medicines information.